1995
DOI: 10.1017/s1357729800013837
|View full text |Cite
|
Sign up to set email alerts
|

Microbial production of skatole in the hind gut of pigs given different diets and its relation to skatole deposition in backfat

Abstract: The intestinal production of skatole and its deposition in backfat was investigated in 35 uncastrated crossbred male pigs. The pigs were fed five purified non-commercial diets containing either casein or brewers yeast slurry as protein source. The yeast slurry diet was used alone or supplemented with either wheat bran (200 g/kg), sugar-beet pulp (200 g/kg), or soya oil (100 g/kg).Skatole concentrations in backfat, and in digesta in different sections of the gastro-intestinal tract were measured at slaughter (m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
181
1
1

Year Published

1999
1999
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 279 publications
(188 citation statements)
references
References 17 publications
1
181
1
1
Order By: Relevance
“…This is in accordance with an earlier study by Knarreborg et al (2002), reporting highly correlated skatole concentrations between faeces and blood. Jensen et al (1995a) also reported correlation between skatole in hindgut and adipose tissue, but large individual differences among animals were observed. The high correlation between skatole and androstenone in adipose tissue observed in the present experiment is in accordance with a study by Zamaratskaia et al (2004b), reporting high correlations between skatole and androstenone in plasma in older pigs (20 weeks).…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…This is in accordance with an earlier study by Knarreborg et al (2002), reporting highly correlated skatole concentrations between faeces and blood. Jensen et al (1995a) also reported correlation between skatole in hindgut and adipose tissue, but large individual differences among animals were observed. The high correlation between skatole and androstenone in adipose tissue observed in the present experiment is in accordance with a study by Zamaratskaia et al (2004b), reporting high correlations between skatole and androstenone in plasma in older pigs (20 weeks).…”
Section: Discussionmentioning
confidence: 93%
“…The digesta from intestine and faeces were analysed for skatole and indole by HPLC as outlined by Jensen and Jensen (1994), with chromatographic conditions described by Hansen-Møller (1994). The SCFA in faeces were analysed by using a modified method of capillary gas chromatography (Jensen et al, 1995a).…”
Section: Dietary Treatmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…The production of skatole greatly depends on the composition of the diet and the intestinal microflora (Jensen et al, 1995;Claus et al, 2003). Important quantities of butyrate are produced when RPS is fermented in the large intestine (Martin et al, 2000;Mentschel and Claus, 2003), which reduces epithelial cell apoptosis .…”
Section: Discussionmentioning
confidence: 99%
“…The concentrations of lactate and VFA (mmol/l) were determined according to a slight modification of the gas chromatography (GC) method of Jensen et al (1995) as described in Missotten et al (2009). The ethanol concentration (mmol/l) was determined with an in-house GC method.…”
Section: Sampling During Trial and At Slaughtermentioning
confidence: 99%